(6).(5)+2.62.(3)=?
@sorumatikbot
(6).(5)+2.62.(3) = ?
To solve this expression, we can follow the order of operations, also known as PEMDAS: Parentheses, Exponents, Multiplication & Division (from left to right), and Addition & Subtraction (from left to right).
Letâ€™s break down the expression step by step:

First, letâ€™s simplify the multiplication: (6).(5) = 30. The negative signs cancel out when multiplying two negative numbers.

Next, we have 2.6 = 12.

Moving on, 2.(3) = 6. Again, the negative sign cancels out when multiplying a negative number by a positive one.
Now, letâ€™s put everything together:
30 + 12  6 = 36
Therefore, the value of the expression (6).(5)+2.62.(3) is equal to 36.
1 Like